High-intensity interval training every second week maintains VO2max in soccer players - Rønnestad, B. R.; Slettaløkken, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The amount of endurance exercise training among semiprofessional soccer players is reduced during the active recovery period between the end of the competition season and start of the preparatory period. Deconditioning before the preparatory period starts can have negative effects as the players have to put in a lot of effort to reach optimal in-season aerobic fitness levels. In the present study we investigated the effect of a 6-week period with one high-intensity aerobic training session (HIT) per week and one HIT every second week on maintenance of aerobic fitness among semiprofessional soccer players. Seventeen male players from the third-highest soccer division in Norway volunteered to participate in this study that took place in the teams` off-season (November to January). The subjects were randomized into one of two groups, either training one HIT per week (Group 1; n = 9) or one HIT every second week (Group 0.5; n = 8). The training session consisted of five bouts of 4 min running at 87-97% of age-predicted maximum heart rate. A 20-m shuttle-run test and VO2max test on a treadmill were performed by all subjects before and after the training intervention. Before the training intervention, distance covered during the 20-m shuttle-run test and VO2max on treadmill were not different between the groups. After 6 weeks of training, distance covered during the 20-m shuttle run was 8% ± 6% lower (p < .01) for Group 1, nonsignificantly 5% ± 10% lower for Group 0.5, and 6% ± 8)% lower when groups were pooled (p < .01). There was no change in VO2max in either of the groups. In conclusion, training one HIT every second week is sufficient for maintaining VO2during a short active recovery period for semiprofessional soccer players. However, performance in a soccer-specific fitness test was slightly reduced.